New layers of regulation of the general stress response sigma factor RpoS - Handler, Simon; Kirkpatrick, Clare L. (Frontiers in Microbiology, 2024)
The general stress response (GSR) sigma factor RpoS from Escherichia coli has emerged as one of the key paradigms for study of how numerous signal inputs are accepted at multiple levels into a single pathway for regulation of gene expression output. While many studies have elucidated the key pathways controlling the production and activity of this sigma factor, recent discoveries have uncovered still more regulatory mechanisms which feed into the network. Moreover, while the regulon of this sigma factor comprises a large proportion of the E. coli genome, the downstream expression levels of all the RpoS target genes are not identically affected by RpoS upregulation but respond heterogeneously, both within and between cells. This minireview highlights the most recent developments in our understanding of RpoS regulation and expression, in particular those which influence the regulatory network at different levels from previously well-studied pathways.